Sand ornaments used to attract females are avoided by rival males in the fiddler crab Uca lactea. Issue 5 (3rd September 2017) - Muramatsu, Daisuke
Abstract : Males of several fiddler crab species sometimes construct sand structures at the entrances to their burrows to which they attract females for mating. Sand structures are thought to exploit fiddler crabs' risk-reducing behaviour by enticing them into the burrows, so males as well as females are expected to be attracted by the structures. Males with structures may thus incur greater costs to repel intruding males than males without structures, and only males that can afford such costs are likely to build structures. Given that the sand structures are constructed only by males that have sufficient ability to fend off intruders, other crabs may regard the structures as an indicator of those males' potential fighting ability. In the present study, I showed that burrowless males of Uca lactea were averse to burrows with structures when there were no predators nearby, but that burrowless females showed no such tendency. Sand structures in fiddler crabs may have originated as a sensory trap to attract females, but other males may use the structure as an indicator of the resident male's fighting ability. However, the sand structures did not appear to function as a signal to attract females.